Multimodality comparison of aorta morphology in patients with aortopathy: 4D flow CMR, CTA, mDIXON - Bastiaan J.C. Te Kiefte; Faeze Gholamiankhah; Joe F. Juffermans; Pieter Van Den Boogaard; Arthur J.H.A. Scholte; Hildo J. Lamb; Jos J.M. Westenberg (BMC Medical Imaging)
Abstract Background Four-dimensional cardiovascular magnetic resonance flow imaging (4D flow CMR) enables analysing of aortic blood flow dynamics. In order to examine the relationship between morphology and hemodynamics, additional anatomical imaging is required. This study aims to assess if 4D flow CMR segmentations can be used to determine morphological parameters by comparing with segmentations from Computed Tomography Angiography (CTA) and mDIXON CMR. Methods This study included 18 patients with various aortic pathologies who underwent CTA and CMR (including mDIXON and 4D flow CMR sequences) of the thoracic aorta. The aortic lumen was segmented from aortic valve to the descending aorta and divided into four anatomical segments: aortic root [AoR], ascending aorta [AAo], aortic arch [AA], and descending aorta [DA]. We compared morphological parameters (maximum diameter, volume, and centreline length) using these different scanning techniques. Segmentations were performed at different cardiac phases: peak systole for CTA and 4D flow CMR, and end-diastole for mDIXON. Results Intraclass Correlation Coefficients (ICCs) and Bland-Altman plots were determined for all modalities and all segments. Agreement between 4D flow CMR and CTA was good to very good for maximum diameter (ICC 0.70–0.85) and centreline length (ICC 0.74–0.90), and very good to excellent for volume (ICC 0.89–0.97). Between mDIXON and CTA very good for maximum diameter (0.89–0.94), good to very good for centreline length (0.78–0.88), and very good to excellent for volume (0.87–0.96). Similar results were found when comparing 4D flow CMR with mDIXON with ICCs for maximum diameter (0.68–0.84), volume (0.91–0.97), and centreline length (0.78–0.90). Statistically significant differences were observed only for maximum diameter in AAo between CTA and mDIXON (p < 0.001), and for volume in AA between CTA and 4D flow CMR (p < 0.001). No significant differences were observed for other segments and parameters. Conclusions Morphologic parameters derived from 4D flow CMR segmentations of the thoracic aorta demonstrate high levels of agreement when compared to segmentations based on CTA and mDIXON, in this relatively small cohort of patients with diverse aortic pathologies. This finding could be of interest for future 4D flow CMR research, as it possibly allows for the evaluation of both morphology and hemodynamics in a single imaging acquisition. Further research in larger cohorts is needed to robustly validate 4D flow CMR as a single-modality imaging technique.